Penerapan Senam Anti Stroke Terhadap Tekanan Darah pada Penderita Hipertensi di Kampungsewu Surakarta - Atifah Sovianasari; Tri Susilowati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: Hypertension or what can be called high blood pressure that occurs when blood vessel pressure is too high, said to be high if the blood pressure is 140/90 mmHg or more. According to the World Health Organization (WHO), the prevalence year is 1.28 billion people who experience hypertension aged 30-79 years. The prevalence of hypertension in Pucangsawit Health Center in 2022 was 4.492 hypertensive patients in Surakarta City, One of the non-pharmacological therapies that can be given to hypertensive patients is anti-stroke gymnastics. Objective: Describe the results of blood pressure comparison and after the application of Anti- Stroke Gymnastics in patients with hypertension. Method: This study uses a descriptive research design with a case study approach by observing blood pressure in 2 respondents with hypertension, conducted 2 weeks for 6x within 30 minutes. The instruments used are observation sheets, Blood Pressure Monitors, and anti-stroke gymnastics SOP videos. Results: There is a decrease in blood pressure after giving Anti-Stroke Gymnastics to Mrs. E from 148/81 mmHg to 130/78 mmHg and to Mrs. S from 157/111 mmHg to 143/101 mmHg. Conclusion: The application of anti-stroke gymnastics can potentially reduce blood pressure in hypertensive patients in both respondents.